Optical coherence tomography angiography biomarkers of microvascular alterations in RVCL-S - Al-Nofal, Mays; de Boer, Irene; Agirman, Seda; Wilms, Anne E.; Zamanipoor Najafabadi, Amir H.; Terwindt, Gisela M.; Notting, Irene C. (Frontiers in Neurology, 2022)
Background The brain and retina share many neuronal and vasculature characteristics. We investigated the retinal microvasculature in patients with a monogenic vasculopathy using optical coherence tomography angiography (OCTA). OCT-A is a novel precise non-invasive imaging method that may provide biomarkers suitable for diagnosis and follow-up of small vessel diseases. Methods In this exploratory cross-sectional study, eleven RVCL-S patients and eleven age-matched healthy control participants were included. The size of the foveal avascular zone (FAZ) and the vascular density of the superficial capillary networks in the retina were measured by OCT-A. Results The symptomatic and presymptomatic patients showed significantly lower vascular density values than controls in the foveal region [median (IQR) 18.2% (15.8–18.6) vs. 24.4% (21.5–26.8) (p < 0.001), 29.8% (29.6–30.8) vs. 33.2% (32.0–33.6) (p = 0.002), respectively]. The FAZ was significantly larger in the symptomatic RVCL-S patients than in the control group [13,416 square pixels [7,529–22,860] vs. 1,405 square pixels [1,344–2,470] (p < 0.001)]. No significant difference was identified in measurements of FAZ comparing presymptomatic and controls. Conclusion Our findings with OCT-A demonstrated that RVCL-S causes an increase in the size of the FAZ in symptomatic RVCL-S patients compared to healthy participants. Moreover, there is a decrease in vessel density in the superficial capillary networks in both symptomatic and presymptomatic patients. In the future, newly developed precise objective instruments such as OCT (-A) may provide important tools in determining disease activity for follow up of common small vessel diseases.